Pola Produksi Sayuran di Kota Pangkalpinang - Karsiningsih, Eni; Atlantika, Ria; Kurniawan, Kori (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
Vegetable production in Pangkalpinang City is very limited because much of the land in Pangkalpinang City is allocated for housing and trade. Vegetable production is mostly carried out by KWT and farmer groups. The obstacles faced by KWT and Farmer Groups are limited land for vegetable farming and production patterns have not been planned properly. This research aims to examine vegetable production patterns in Pangkalpinang City. The descriptive analysis method is used to determine vegetable production patterns. The research results show that vegetable farming by KWT is carried out using soil and hydroponics. Meanwhile, the Farmer Group only uses soil as a medium. There are 17 patterns of vegetable production using soil media and 8 patterns of vegetable production using hydroponics. Setting vegetable planting patterns is useful for regulating the amount of production and variety of vegetables.